Safety of nanomaterials along their lifecycle : release, exposure, and human hazards - Wohlleben, Wendel (Boca Raton : CRC Press, 2015)
'Billions of dollars in public funding have been spent on novel nanomaterials, and the resulting products are entering the consumer world now: new paints and coatings; electric cars powered by nanomaterials in the battery, chassis, and tires; new renewable energy sources, to name a few. But contrary to other disrupting technologies such as nuclear energy or genetics, the scientific community has started to investigate the risks associated with novel nanomaterials early in the development phase. Although there are still gaps in our knowledge of the risks presented by nanomaterials, we now know enough to describe scenarios that are too high-risk to implement as well as scenarios for the safe use of nanomaterials. The goal of this book is to help the reader in making such safely decisions'--
Includes bibliographical references and index.
Keywords: Nanostructured materials -- Environmental aspects; Nanostructured materials -- Health aspects; Nanoparticles -- Toxicology